2020
DOI: 10.1177/1073274820956615
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics as Predictors of Outcomes in Hepatocellular Carcinoma: A Retrospective Cohort Study

Abstract: Background: Race, gender, insurance status, and income play important roles in predicting health care outcomes. However, the impact of these factors has yet to be fully elucidated in the setting of hepatocellular carcinoma (HCC). Methods: We designed a retrospective cohort study utilizing data from the Surveillance, Epidemiology, and End Results (SEER) program to identify patients diagnosed with resectable HCC (N = 28,518). Demographic factors of interest included race (Asian/Pacific Islander [API], African Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although research in the United States has suggested that factors such as racial disparities and insurance status may affect liver cancer survival rates, 2 it remains to be seen whether these conclusions can be applied to Taiwan, a predominantly homogeneous population with universal healthcare coverage, and this aspect deserves further investigation. Unfortunately, the specific surgical techniques and choices of anesthetic drugs could not be presented in the database.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Although research in the United States has suggested that factors such as racial disparities and insurance status may affect liver cancer survival rates, 2 it remains to be seen whether these conclusions can be applied to Taiwan, a predominantly homogeneous population with universal healthcare coverage, and this aspect deserves further investigation. Unfortunately, the specific surgical techniques and choices of anesthetic drugs could not be presented in the database.…”
Section: Letter To the Editormentioning
confidence: 99%
“…It has been well-documented that race and socioeconomic status have been associated with worse outcomes and higher rates of mortality after emergency general surgery, and surgery for gastric adenocarcinoma, hepatocellular carcinoma, and gastric adenocarcinoma. [6][7][8][9] It is, therefore, possible that race and socioeconomic status influence outcomes after ground-level falls in patients aged >60; however, for our group of patients, this was not the case.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, the most common risk factor for HCC globally is the hepatitis B virus. In a previous study, the most common causative agent was the hepatitis C virus [3]. More than 90% of primary liver cancers are HCC [4].…”
Section: Introductionmentioning
confidence: 96%